Making North America : trade, security, and integration - Thompson, James, 1975- (University of Toronto Press, 2014)
In Making North America, James Thompson uses the Canada-US Free Trade Agreement of 1988 and the North American Free Trade Agreement of 1994 to demonstrate that there has been an often-unrecognized impulse behind the process of North American integration - national security.